Eosinophilic Solid and Cystic (ESC) Renal Cell Carcinomas Harbor TSC Mutations: Molecular Analysis Supports an Expanding Clinicopathologic Spectrum. (September 2018) - Palsgrove, Doreen N.; Li, Yunjie; Pratilas, Christine A.; Lin, Ming-Tseh; Pallavajjalla, Aparna; Gocke, Christopher; De Marzo, Angelo M.; Matoso, Andres; Netto, George J.; Epstein, Jonathan I.; Argani, Pedram
Abstract : Eosinophilic solid and cystic (ESC) renal cell carcinoma (RCC) has recently been described as a potentially new subtype of RCC based upon morphologic and immunohistochemical features. These neoplasms typically demonstrate solid and cystic architecture, and the neoplastic cells contain voluminous eosinophilic cytoplasm with granular cytoplasmic stippling. There is frequently focal immunoreactivity for cytokeratin 20. Although the initial cases all occurred in adult females and had benign outcome, we recently expanded the proposed spectrum of this neoplasm to include pediatric cases, multifocal neoplasms, and a case with hematogenous metastasis. ESC has been postulated to be analogous to a subtype of RCC consistently identified in tuberous sclerosis complex patients, and while previous work has demonstrated loss of heterozygosity at the TSC1 locus and copy number gains at TSC2 in ESC RCC, these genes have not been sequenced in ESC RCC. Using capture-based and amplicon-based next-generation sequencing, we now demonstrate the consistent presence of either TSC1 or TSC2 gene mutations in pediatric ESC RCC (8/9 cases) and adult ESC RCC (6/6 cases). These included a metastatic ESC RCC which had a complete response to mTOR targeted therapy. We also found these mutations in some neoplasms with variant morphology and thus potentially expand the spectrum of ESC RCC. These include one of our adult cases which demonstrated dominant "type 2" papillary RCC morphology and 2 of 3 previously unclassified pediatric RCC with features of ESC RCC minus granular cytoplasmic stippling. We also demonstrate TSC mutations in a case of so-called "oncocytoid RCC after neuroblastoma" with identical morphology and immunoprofile, providing a molecular link between the latter and ESC RCC. In summary, ESC RCC consistently harbors actionable TSC1 or TSC2 mutations, which are infrequently seen in established subtypes of RCC. These findings support TSC1/2 mutation as a molecular marker of ESC RCC, and suggest expansion of the clinicopathologic spectrum to include neoplasms with papillary architecture, occasional cases lacking well-developed granular cytoplasmic stippling, and a subset of RCC with oncocytic features in patients who have survived neuroblastoma. Abstract : Supplemental Digital Content is available in the text.